Reflections on musical meaning and its representations - Treitler, Leo, 1931-; Indiana University. Press (Bloomington : Indiana University Press, 2011)
In this collection of thoroughly revised essays and lectures, distinguished scholar Leo Treitler explores the relationships among language, musical notation, performance, compositional practice, and patterns of culture in the presentation and representation of music. Treitler engages a wide variety of historical sources to discuss works from medieval plainchant to Berg's opera Lulu and a range of music in between.--[book cover]
-- Language. Language and the interpretation of music ; Being at a loss for words ; Beethoven's "expressive" markings -- Performance. The immanence of performance in medieval song ; Early recorded performances of Chopin waltzes and mazurkas : the relation to the text -- Notation. What kind of thing is musical notation? ; Sketching music, writing music -- Interpretative frames. The Lulu character and the character of Lulu ; History and archetypes ; Gender and other dualities of music history ; Hermeneutics, exegetics, or what? ; Facile metaphors, hidden gaps, short circuits : should we adore Adorno?
Includes bibliographical references (pages 289-304) and index.
Keywords: Music -- Philosophy and aesthetics; Music -- History and criticism